Antibacterial quaternary ammonium chitosan/carboxymethyl starch/alginate sponges with enhanced hemostatic property for the prevention of dry socket - Deng, Xuyang; Wang, Danyang; Zhang, Dongjie; Sun, Ming; Zhou, Liying; Wang, Yuxi; Kong, Xiaowen; Yuan, Changqing; Zhou, Qihui (Frontiers in Bioengineering and Biotechnology, 2023)
Tooth extraction commonly leads to postoperative wound bleeding, bacterial infection, and even the occurrence of dry socket. Therefore, developing a biomedical material with favorable antibacterial and excellent hemostatic properties to prevent the post-extraction dry socket is necessary. Herein, quaternary ammonium chitosan/ carboxymethyl starch/alginate (ACQ) sponges are developed via Ca2+ cross-linking, electrostatic interaction, and lyophilization methods. The results show that the bio-multifunctional sponges exhibit interconnected porous structures with significant fluid absorption rates and suitable water vapor transmission rates. In vitro cellular and hemolysis experiments indicate that the developed sponges have acceptable biocompatibility. Notably, the constructed sponges effectively inhibit the growth of E. coli, S. aureus, and C. albicans, as well as achieve rapid hemostasis in the mouse liver injury and mini-pig tooth extraction models by absorbing blood and promoting red blood cell adhesion. Thus, the created bio-multifunctional sponges show tremendous promise as a hemostatic material for wound management after tooth extraction.